Relationship between the development of the spear leaf and the weight of the foliar heart of peach palm (Bactris gasipaes Kunth). - Arroyo-Oquendo, Carlos (2003)
The varieties used were developed fromgermplasm coming from three different geographical regions,Diamantes-10 and Diamantes-20 from the High Amazon areaand Panamá, respectively; and Diamantes-1 and Utilis-Tucurrique from Costa Rica. The results showed differencesamong them. One example of the spectrum of correlations andregressions obtained in this work, is the synchronism ofdevelopment among the leaf parts . sheath, petiole and blade .which is greater in the varieties Utilis-Tucurrique andDiamantes-1 than in the other two. The last two differ betweenthemselves in several aspects. For the correlation betweenfoliar heart of palm weight and sheath length of the spear leaf,the variety Diamantes-1 shows the highest coefficient (r =0.83), followed by Utilis-Tucurrique (r = 0.77), whileDiamantes-10 and Diamantes-20 had lower values (r = 0.60 and0.57 respectively). The correlation between foliar heart of palmweight and the degree of opening of the spear leaf lamina islarger for Diamantes-1 (r = 0.86) than for Utilis-Tucurrique (r =0.76) and Diamantes-10 and Diamantes-20 (r = 0.71 and 0.70respectively). From those results it is clear that the predictionof the maximum weight reached by the foliar heart of palm ismore accurate in Diamantes-1 (r = 0.86) than in the other threevarieties (r = 0.76, 0.71 and 0.70). The regression curvesclearly show the best spear leaf blade opening stages to harvestfor each variety. Besides, there is no correlation between thedegree of opening of the spear leaf blade and the caulinar heartof palm weight.